Divergence of gut bacteria through the selection of genomic variants implicated in the metabolism of sugars, amino acids, and purines by small extracellular vesicles in milk - Fang Zhou; Peerzada Tajamul Mumtaz; Haluk Dogan; Roland Madadjim; Juan Cui; Janos Zempleni (Gut Microbes)
Here, we report that small extracellular vesicles (sEVs) in milk mediate the communication between bacteria and animal kingdoms, increase the divergence of bacteria in the intestine, and alter metabolite production by bacteria. We show that bovine milk sEVs select approximately 55,000 genomic variants in 19 species of bacteria from the murine cecum ex vivo. The genomic variants are transcribed into mRNA. The selection of genomic variants by milk sEVs alters bacterial metabolism, leading to an up to 12-fold difference in the abundance of more than 1000 metabolites in bacteria cultured in milk sEV-free media compared to sEV-containing media. Evidence is particularly strong that selection of genomic variants by milk sEV changes the metabolism of sugars, amino acids, and purines which might contribute to the development of spatial learning and memory deficiencies and seizure phenotypes reported for milk sEV-depleted infants and mice. Human milk is a rich source of sEVs, whereas formula contains only trace amounts of milk sEVs. This report implicates nutritional sEVs in altered microbial metabolism beyond the mere selection of bacterial communities.